1969
DOI: 10.2307/1936263
|View full text |Cite
|
Sign up to set email alerts
|

Periodicity and Energetics of Torpor in the Kangaroo Mouse, Microdipodops Pallidus

Abstract: The effects of three environmental temperatures and four food rations on the duration and periodicity of torpor were examined, the oxygen consumption of torpid and normothermic kangaroo mice was measured, and temperature profiles in their habitat were obtained during all seasons. Because of their fossorial and nocturnal habits, kangaroo mice need not face environmental temperature above 30°C or much below 0°C although temperatures in their Great Basin habitat normally fluctuate far outside this range. Torpidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(24 citation statements)
references
References 6 publications
0
24
0
Order By: Relevance
“…Other species are apparently capable of using torpor to manage unpredictable supplies of food (Brown and Bartholomew 1969) or water (Ibuka and Fukumara 1997). But what is important in our study is that we have controlled food intakes in a manner that induced torpor responses to a pattern of unpredictability, rather than simply providing a different level of energy restriction.…”
Section: Discussionmentioning
confidence: 99%
“…Other species are apparently capable of using torpor to manage unpredictable supplies of food (Brown and Bartholomew 1969) or water (Ibuka and Fukumara 1997). But what is important in our study is that we have controlled food intakes in a manner that induced torpor responses to a pattern of unpredictability, rather than simply providing a different level of energy restriction.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies under constant T a have found that whereas times of entry into torpor are variable and occur earlier in the active phase under conditions of energetic stress, times of arousal appear largely fixed according to an endogenous circadian rhythm (Tucker, 1962;Brown and Bartholomew, 1969;Geiser, 1986). By contrast, in wild animals, times of arousal frequently coincide with an initial period of passive rewarming during the day , suggesting that these arousals are triggered by a threshold level of exogenous rewarming (Schmid, 1996;Lovegrove et al, 1999;Körtner and Geiser, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In a similar fashion, kangaroo mice (Microdipodops pallidus) increasingly employ torpor in response to food restriction, enabling them not only to maintain body mass but also to accumulate food stores (Brown and Bartholomew 1969). It therefore appears that, similar to hibernation, in some species, daily torpor can be used to shift energetic costs between seasons beyond simply balancing daily energy requirements.…”
Section: Discussionmentioning
confidence: 99%